Sutureless Aortic Prosthesis Implantation: the First Brazilian Experience with Perceval Device - Tagliari,Ana Paula (2016)
Abstract This is a report of the first Brazilian experience with the Perceval sutureless aortic prosthesis in two patients with severe aortic stenosis. Transesophageal echocardiography was used during the procedure. The aortotomy was performed 1 cm above the sinotubular junction, followed by leaflets removal and decalcification. Correct valve size was selected, device released and an accommodation balloon used. The cardiopulmonary bypass times were 47 and 38 min and the cross-clamp times were 38 and 30 min. There was a significant decrease in mean gradients (41 and 75 mmHg preoperatively; 7 and 8 mmHg postoperatively). There was no major complication or paravalvular leak.